Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Belajar IPS Pada Siswa Kelas IV SD Inpres Lansot - Kalangi, Sefia; Pinontoan, Marien; Mottoh, Yulmi H. (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to improve social studies learning outcomes on Ethnic and Cultural Diversity material through the application of the Problem-Based learning model for fourth grade students at SD Inpres Lansot. This research was carried out using the Classroom Action Research method according to Kemmis and Mc. Taggart (Aqid Zainal, 2006:31), which consists of four stages, namely Planning, Implementation/Action, Observation, and Reflection. The data collection techniques used in this research were observation and test sheets, namely assessment sheets (LP) and student worksheets (LKS). The data analysis technique uses the formula (Trianto, 2008: 171) KB = T/Tt x 100%. Student learning outcomes in cycle I only reached 62%, while in cycle II it reached 84%. It can be concluded that implementing the Problem Based learning model can improve social studies learning outcomes with material on ethnic and cultural diversity in class IV students at SD Inpres Lansot and can help students to be more advised to apply the Problem Based learning model in social studies learning